PENGARUH SELF EFFICACY DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN (Studi Pada Ramayana Mal Bali) - Ary, Iwan Restu; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen, 2019)
ABSTRACT   Performance becomes the real foundation for the organization because without the performance of the objectives owned by the organization cannot be achieved. This study aims to describe the influence of self efficacy and locus of control to employee performance study on Ramayana Mal Bali. This research was conducted at Ramayana Mal Bali Company. The number of samples used are 64 employees, with simple random sampling method. Data from this research are primary data obtained from observation, interview and questionnaire distribution. The analysis technique used is multiple linear regression. Based on the results of the analysis that has been done can be concluded that self efficacy has a positive and significant effect on employee performance. Locus of control has a positive and significant effect on employee performance. Self efficacy and locus of control together affect the employee performance.   Keywords : employee performance, self efficacy, locus of control